The Impact of Volunteerism on Community Resilience in Disaster Management - Marti Ganoe; Joyner Roslida; Togarman Sihotang (Insan Akademika Publications, 2023)
This research investigates the indispensable role of volunteers in disaster management and their profound impact on communities grappling with the aftermath of natural disasters. The study comprehensively explores the motivations that propel volunteers into action, their effectiveness in disaster response, and the far-reaching consequences of their involvement. The primary motivation of volunteers is revealed to be altruism, accompanied by a strong sense of duty and personal experience with disasters. Their effectiveness in disaster management is evident in their rapid response times and versatile contributions, complementing formal emergency services. Importantly, the impact of volunteers extends beyond immediate relief efforts, fostering heightened community resilience, accelerated economic recovery, improved psychological well-being among survivors, and community empowerment. The research also highlights the need for nuanced investigations into the psychological well-being of volunteers, the influence of cultural contexts on volunteer motivations, and ethical considerations within the framework of disaster volunteering. This study underscores the transformative potential of volunteers in disaster management and calls for policies and practices that recognize, empower, and support these altruistic individuals. By fostering a culture of volunteerism and enhancing disaster preparedness, response, and recovery efforts, communities can become more resilient and better equipped to navigate the challenges posed by natural disasters.